2017
DOI: 10.1109/rbme.2017.2694142
|View full text |Cite
|
Sign up to set email alerts
|

Human Factors and Neurophysiological Metrics in Air Traffic Control: A Critical Review

Abstract: This paper provides a focused and organized review of the research progress on neurophysiological indicators, also called "neurometrics," to show how they can effectively address some of the most important human factors (HFs) needs in the air traffic management (ATM) field. In order to better understand and highlight available opportunities of such neuroscientific applications, state of the art on the most involved HFs and related cognitive processes (e.g., mental workload and cognitive training) are presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 94 publications
(105 reference statements)
0
69
0
Order By: Relevance
“…Neurophysiological measures, such as the electroencephalographic signal (EEG), allow the objective assessment of the cognitive state under which the user is performing the considered task. The effectiveness of this approach has already been explored in a variety of applications ranging from human-robot interaction to training protocols assessment, car driving, and air-traffic-control itself, even by the authors of the present work [16,37,[58][59][60]. In the scientific literature, it has been widely demonstrated that the higher sensitivity of neurophysiological measurement compared to conventional techniques, such as the questionnaires, is more effective as traditional methods require a larger subject sample to highlight the same effect.…”
Section: The Study Rationale: Laboratory Models and Ecological Validamentioning
confidence: 88%
See 1 more Smart Citation
“…Neurophysiological measures, such as the electroencephalographic signal (EEG), allow the objective assessment of the cognitive state under which the user is performing the considered task. The effectiveness of this approach has already been explored in a variety of applications ranging from human-robot interaction to training protocols assessment, car driving, and air-traffic-control itself, even by the authors of the present work [16,37,[58][59][60]. In the scientific literature, it has been widely demonstrated that the higher sensitivity of neurophysiological measurement compared to conventional techniques, such as the questionnaires, is more effective as traditional methods require a larger subject sample to highlight the same effect.…”
Section: The Study Rationale: Laboratory Models and Ecological Validamentioning
confidence: 88%
“…Today, in many industrial and military systems, the importance of predicting vigilance dynamics for assessing human performances is largely accepted; in fact, several studies show that accidents are often the results of vigilance failures [34,35]. The reduction of vigilance and sensitivity to important signals, for example, infrequent but critical ones, was observed in the domain in which the level of automation was very high, as in aviation [36,37], nuclear power plants [38] and the Stock Market [39].…”
Section: Current Key Research Points On Vigilancementioning
confidence: 99%
“…Latter is particularly relevant in safety-critical occupations with high cognitive demands and responsibility, such as air traffic control. A valid and reliable method for measuring mental workload would offer a way for achieving such conditions in human-machine systems by capturing the instantaneous workload continuously over time (Byrne and Parasuraman, 1996;Scerbo et al, 2001;Arico et al, 2017). It is important that the registration method does not interact with the task or alter subject's mental state by imposing additional demands as it is the case during subjective assessment of workload by means of questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, task difficulty could have effects on the amount of mental resources employed by the subject to deal with the task demand, that is the definition of mental workload. Mental workload can be estimate by means of behavioral and subjective measures [ 10 ], but it has also been demonstrated that mental workload variations correlate with changes in EEG spectral power, in particular an increase in the EEG theta band (4–7 Hz) over the frontal cortex, and a decrease in the EEG alpha band (8–12 Hz) over the parietal cortex [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%